Estrategias de crecimiento para la Cooperativa de Ahorro y Crédito 29 de enero del cantón Chaguarpamba periodo 2019-2024 - Ayala Cuenca, José Luis (2019)
This thesis is a descriptive type of research, which was applied to the Savings and Loan Cooperative "29 JANUARY" in the canton of Chaguarpamba, in order to offer solutions to the problems currently facing the entity, improving competitive efficiency, improving its performance and increasing levels of participation and growth in the financial sector. The descriptive methodology served to define, classify, describe and identify the main problems, the same that arose from the analysis of internal and external factors establishing, thereby the Strengths, Weaknesses, Opportunities and Threats of the entity; from the collection of information through the application of an interview conducted with the manager. As well as a Survey to the members of the cooperative which allowed to collect information and to know the current situation of the entity. The fundamental part of the work focused on carrying out the situational analysis from which the necessary information was obtained to prepare the factor evaluation matrix (FEM), as well as the completion of the MPC competitive profile matrix. The analysis of internal factors was also carried out, for which purpose the Partner Surveys and the financial diagnosis were applied with the application of vertical and horizontal financial analyses, application of SEPS financial indicators; the information obtained served as the basis for the elaboration of the internal factors evaluation matrix (EFI). With the information obtained through the analysis of both external and internal factors, the SWOT matrix was prepared, which led to the strategies for this entity. The structure of the strategic objectives is nuanced by the determination of Strategy, Activities, Policy, Lines of Action, Resources, Time, Responsible for their fulfillment, Expected Results, and Budget. In the complementary part, the conclusions are recorded with the respective recommendations, which generate an important contribution in the research carried out. The work was applied in a population of 2330 partners where a sample of 327 people was determined and a survey was carried out to obtain the necessary information for the development of the objectives. Finally, it is deduced that there is inefficiency in the placement of credits, produced mainly by factors such as an inadequate analysis of the applicant's income, scarce information and lack of guarantees, which is why the delinquency of the credits granted is high; this is why it is recommended to apply a policy of restructuring expired credits that allows dialogue with the partners offering them facilities in their payments and longer terms in order to achieve liquidity and economic solvency.